Invisible colleges revealed: Professional networks and personal interconnections amongst adult educators - Nod Miller (Adult Education Research Conference, 1994)
This paper describes some findings from a study conducted in Australia to investigate professional networks (or invisible colleges) and personal interconnections amongst university-based adult educators. The importance of such networks in personal career terms and in the development of professional cultures is analysed. The significance of conferences, e-mail and 'opinion leaders' in the formation and maintenance of invisible colleges is discussed and power relations and patterns of influence are examined.